Occurrence of Pregnancies among HIV Infected Indian Women: Does Knowledge about HIV Status Make a Difference?. (24th February 2015) - Darak, Shrinivas; Hutter, Inge; Kulkarni, Sanjeevani; Kulkarni, Vinay; Janssen, Fanny
Abstract : This is the first study to examine the behavioural effect of HIV on fertility among HIV infected women in India. Retrospective calendar data from ever-married HIV infected women between 15 and 45 years of age, attending a specialized HIV clinic in Pune, Western India ( N = 560 ), were analysed. Directly standardized overall and parity-specific pregnancy rates were compared among HIV infected women before and after coming to know about their HIV status. The age- and parity-standardized pregnancy rates and age-standardized parity-specific pregnancy rates were statistically significantly lower after knowing about HIV status as compared to before the HIV status was known. Analysis of parity-specific rates suggested lower likelihood of HIV infected women to progress to higher parity. The clear behavioural impact of HIV on fertility observed should be taken into account while estimating HIV infected pregnant women in the country. Ensuring access to information and services for PMTCT to HIV infected couples is essential to support informed reproductive decision making among them.